Comparative Study of Indonesian Spectra Response Parameters for Buildings According To 2012 and 2019 Seismic Codes - Faizah, Restu; Amaliah, Rahma (International Journal of Integrated Engineering, 2021)
The Indonesian government has determined a new seismic code for structural design of buildings and non-buildings, namely SNI 1726:2019. This new code is a revision of the previous code of 2012. The fundamental difference between the two seismic codes of 2012 and 2019 is in the earthquake hazard map (EHM) that was used.  2012 seismic code uses the EHM-2010, while 2019 seismic code uses the EHM-2017. The EHM-2017 has been updated by revising a data of subduction parameters and updating the number of active faults from 81 to 251. This revision has an impact on increasing the spectral value of SS and S1 which is a parameter that must be reviewed in structural planning. This study investigated the seismicity status of 34 cities in Indonesia by comparing the values of the spectra response parameters (SDS and SD1) according to seismic code of 2012 and 2019. This study found that the SDS and SD1 value from 2012 to 2019 increased in 15 cities but decreased or remained in 19 other cities. The cities that experienced an increase of SDS and SD1 values were Bandar Lampung, Banjarmasin, Bengkulu, Gorontalo, Jayapura, Manokrawi, Medan, Palembang, Palu, Pangkal Pinang, Pontianak, Serang, Surabaya, Tanjung Selor, and Yogyakarta. It seems that the vulnerability assessment of the existing building in the 15 cities must be done to estimate their capacity under earthquake load designed by 2019 Seismic Code. Overall, Jayapura city has the highest of SDS and SD1 values in 2019 compared to the other cities.